Analisis Pengaruh Indeks Bursa Negara Lain (KOSPI, HANGSENG, FTSE, DJIA, NIKKEI) Terhadap Indeks Harga Saham gabungan (IHSG) Bursa Efek Indonesia Selama Periode 2000-2010 - , Hari Purnomo ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This paper examines correlation and the effect of regional indices, KOSPI, HANGSENG, FTSE, DJIA and NIKKEI to Indonesia Stock Exchange Composite Stock Price Index, IHSG on the period of the year 2000 to 2010. The movement of IHSG apparently more or less is influenced by the movement of the regional indices. During the year of 1997âs Asian financial crisis and the year of 2008, some researchers show most of these exchange indices declined significantly. The methodology used in this paper is multiple linear regression. We found that KOSPI, HANGSENG and NIKKEI have positive coefficient regression and they influence IHSG significantly. And HANGSENG index individually has positive coefficient regression and influence IHSG significantly. But other regional indices, KOSPI and NIKKEI have no significant coefficient regression and have not influenced IHSG significantly.